PENERAPAN METODE THINK PAIR SHARE DALAM UPAYA MENINGKATKAN HASIL BELAJAR SISWA - TRI SUTRISNO (EBTIDA': Jurnal Pendidikan Dasar Islam, 2023)
Abstract Mathematics material becomes a 'scourge' for some students. Monotonous learning adds to the boredom of children learning mathematics. Mathematics teachers are required to be a fun educator figure so that the material can be absorbed properly. Based on the results of initial observations at SDN Kalianget Barat 1, it was found that from the number of students as many as 16 students in grade 6, there were 10 students who did not complete theme 1, sub-theme 1, mathematics. The tendency is that they think negatively about mathematics. As if mathematics is a scary subject, difficult, complicated and full of counting numbers. Even though teaching mathematics is not only with numbers that make students bored and less attractive. Teaching mathematics in elementary school (SD) classes does require a special method to make it fun and challenging. The Think Pair Share method is tried to be a model to overcome such problems. This improvement uses classroom action research (CAR), with the hope that the Think Pair Share method can improve student learning outcomes. Based on the results of the study that the use of the Think Pair Share method with good implementation can improve learning outcomes, it is stated from the results of the presentation that in the first cycle the number of children who completed as many as 4 people or 25%, while in the second cycle, the number of students who completed as many as 12 people or 75%, meaning the increase is read as much as 50%. From these data it can be concluded that the implementation of the Think Pair Share learning method can improve learning outcomes.